Empedocles: Divinization and Suicide - Avanesov, Sergey (SCHOLE, 2007)
In his article on Empedocles Sergej Anavesov of Tomsk State University presents a part of his bigger study in the philosophy of suicide, and shows that Empedocles’ famous deed can be understood as an act of “metaphysical revolt”, a mysterious purification of the soul from the body and the universe from the evil elements. The article is a developed version of a paper presented by the author in May 2007 at the conference “Rethinking Dodds. Rationalism and Irrationalism in Ancient Philosophical Tradition”, organized by the Centre for Ancient Philosophy and the Classical Tradition at the Institute of Philosophy and Law of the Siberian Branch of Russian Academy of Sciences.